Efektivitas Layanan Konseling Kelompok Menggunakan Teknik Problem Solving dalam Menurunkan Perilaku Membolos Siswa - M Fatchurahman; Dina Fariza Triyani Syarif; Siti Turohmi (Universitas Mathla'ul Anwar Banten, 2018)
THE EFFECTIVENESS OF GROUP COUNSELING SERVICES USING PROBLEM SOLVING TECHNIQUES IN REDUCING STUDENTS TRUANT BEHAVIOR. Various problems faced by the student counselor at school. One of the problem is truant during the school hours. Truant behavior of the student with a wide variety of reasons as a form of defending himself in order not to get a penalty. This research was conducted in order to determine the effectiveness of group counseling services to problem solving techniques in reducing truant behavior among students of class X SMAN 2 Palangkaraya. This type of research is the approach of the Pre-Experiment without any form of class control with One-group pretest-posttest design. Subjects were students of class XI in High School Mathematics 2 Palangkaraya of 8 people identified as having truant. Research data collection using a scale. Data analysis using Paired Samples T Test with rocky SPSS software version 20.00. The results showed that the group counseling services to problem solving technique was effective in reducing the truant behavior of students at SMA Negeri 2 Palangkaraya.